Two-decade variability of climatic factors and its effect on the link between photosynthesis and meteorological parameters : example of Finland's boreal forest - Pysarenko, Larysa; Krakovska, Svitlana; Savenets, Mykhailo; Ezhova, Ekaterina; Lintunen, Anna; Petäjä, Tuukka; Bäck, Jaana; Kulmala, Markku (Finnish Environment Institute, 2022)
Climate and forests are linked to each other via sophisticated feedback mechanisms. Recognizing the complexity of atmosphere-biosphere interactions, here we use a simplified approach aiming to establish connections between the parameters characterizing the boreal forest as a carbon sink and meteorological parameters using a two-decade data set (1996-2017) from the Station for Measuring Ecosystem - Atmosphere Relations (SMEAR II), Finland. First, we quantify climate changes in Finland using growing season length and climatic indices. Then we apply the indices to determine unusually cold, warm, wet, or dry years as compared with the typical conditions at SMEAR II. Further, we analyze the relationships between air temperature, precipitation, absorbed photosynthetically active radiation (PAR) and atmospheric CO2 concentration. Our results suggest increased photosynthesis in the Finnish boreal forest with warming and emphasize the importance of long-term measurements for integrated atmosphere-biosphere studies. Peer reviewed